From Fish Port City to the County Capital: Idi City, 1974-2020 - Feliza Reffina (Riwayat: Educational Journal of History and Humanities, 2022)
Idi city an administrative city thas has the main function as the adminisrative center of East Aceh Regency, this city is known as an area that has various historical heritages that are still preserved today. The purpose of thish research was to explain the development and process of ecological change in Idi City from a fish port city the district capital in 1974-2020. This research methods using a qualitative appproach. The data collection techniques used are documentation, literature review, and interviews. The results of the research showed that, City of Idi has always been known as the center of government during the dutch Colonial period, at which time Idi City had become the center of the discretion of East Aceh Regency. After the colonial period ended, Idi City began to change from the center of government into a fishing port city. Ecologically Idi revedeveloped after being designated as the capital of East Aceh Regency. After Idi Rayeuk was established as the district capital, Idi City became one of the most developed cities in East Aceh Regency. The development of the city of Idi can be seen from the housing and settlement center, office center, and trade center.